Genome-wide analysis of AP2/ERF transcription factors in zoysiagrass, Zoysia japonica - Jinyue Zhao (Biotechnology & Biotechnological Equipment, 2018)
The AP2/ERF (AP2, APETALA2; ERF, ethylene responsive factor) transcription factors regulate various important processes in plants, including growth, development, metabolism and stress responses. In the zoysiagrass genome (Zoysia japonica), 147 AP2/ERF genes were identified, which were classified into three families based on phylogenetic analysis. By analysis of RNA-sequencing data, the expression profiles of 46 members were assessed, and their regulation patterns in response to cold stress were investigated. Meanwhile, a zoysiagrass genetic regulation network (GRN) was reconstructed based on rice interaction data using the homology search method. Two GRN modules containing AP2/ERF transcription factors were characterized as having important functions in exocytosis and sucrose metabolism processes, which suggested that AP2/ERF transcription factors play critical roles in these biological processes, exerting control over plant growth and stress responses. These results provide useful information for future functional analyses of the AP2/ERF family in zoysiagrass.